Food Fundamentals Workbook - Joy C. Jordan; Linda D. Cook (EDIS)
4-H FOOD FUNdamentals will introduce you to the fundamentals of health, nutrition and fitness. There are nine fundamental topics to help you score with PYRAMID POWER! This information was published October 1994, as 4HFNM12, Florida Cooperative Extension Service. Revised March 1999. Reviewed June 2002. Printed October 2002.